2021
DOI: 10.1016/j.eclinm.2021.100889
|View full text |Cite
|
Sign up to set email alerts
|

The influence of modifiable risk factors on short-term postoperative outcomes following cervical spine surgery: A retrospective propensity score matched analysis

Abstract: Background: Modifiable risk factors (MRFs) represent patient variables associated with increased complication rates that may be prevented. There exists a paucity of studies that comprehensively analyze MRF subgroups and their independent association with postoperative complications in patients undergoing cervical spine surgery. Therefore, the purpose of this study is to compare outcomes between patients receiving cervical spine surgery with reported MRFs. Methods: Retrospective analysis of the Nationwide Readm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…While comorbidity indices such as CCI and ECI create one score accounting for all comorbidities present within a patient, previous studies have evaluated the influence of specific risk factor categories on patient outcomes following spine surgery. Within the domain of cervical spine surgery specifically, a prior study by Shahrestani et al 17 demonstrated that substance abuse (SA), vascular (V), and dietary (D) MRFs may uniquely influence postoperative outcomes following cervical spine fusion procedures. Using a combined comorbidity score such as ECI, we still capture SA, V, and D diagnoses as individual points added to an overall score, but lose some granularity in terms of comorbidity etiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While comorbidity indices such as CCI and ECI create one score accounting for all comorbidities present within a patient, previous studies have evaluated the influence of specific risk factor categories on patient outcomes following spine surgery. Within the domain of cervical spine surgery specifically, a prior study by Shahrestani et al 17 demonstrated that substance abuse (SA), vascular (V), and dietary (D) MRFs may uniquely influence postoperative outcomes following cervical spine fusion procedures. Using a combined comorbidity score such as ECI, we still capture SA, V, and D diagnoses as individual points added to an overall score, but lose some granularity in terms of comorbidity etiology.…”
Section: Discussionmentioning
confidence: 99%
“…With the analytical advantages of big data and machine learning, we are now entering an era where training and clinical experience can be enhanced with the aid of high data density diagnostics, prognostication, and outcomes prediction. Utilizing these tools with large multicenter collaborative efforts such as nationally representative outcomes databases, studies have found that morbidity and mortality in cervical fusion surgery are associated with specific characteristics: age, [13][14][15] modifiable risk factors (MRFs) such as obesity and malnutrition, [16][17][18][19] and the influence of certain nonmodifiable factors, for example, frailty. 20,21 For these reasons, comorbidity indices such as the Elixhauser Comorbidity Index (ECI) and Charlson Comorbidity Index (CCI) have been developed to augment clinical prognostication efforts.…”
mentioning
confidence: 99%
“…PSM analysis strategies, such as tumor chemotherapy ( 47 ), cervical spine surgery ( 48 ), robot-assisted surgery ( 49 ), and other areas, are widely used in medical research. The PSM analysis can reduce the difference between the two groups of comparable data and decrease the effect of interfering factors on the results by adjusting the balance of baseline data ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Some modifiable risk factors for complications after lumbar fusion include substance abuse, such as alcohol, opioids, and tobacco use, hypertension, dyslipidemia, malnutrition, and obesity. 5 Tobacco use is a prevalent modifiable risk factor that has been demonstrated to be associated with wound complications, deep infections, and pseudarthrosis, as well as an increase in the risk of inhospital mortality in patients undergoing orthopedic procedures. 6,7 Tobacco use includes both smoking and smokeless tobacco, such as e-cigarettes or chewing tobacco.…”
mentioning
confidence: 99%